Interventions for tobacco cessation delivered by dental professionals - Holliday, Richard (Cochrane Database Syst Rev, 2021)
BACKGROUND: Dental professionals are well placed to help their patients stop using tobacco products. Large proportions of the population visit the dentist regularly. In addition, the adverse effects of tobacco use on oral health provide a context that dental professionals can use to motivate a quit attempt. OBJECTIVES: To assess the effectiveness, adverse events and oral health effects of tobacco cessation interventions offered by dental professionals. SEARCH METHODS: We searched the Cochrane Tobacco Addiction Group's Specialised Register up to February 2020. SELECTION CRITERIA: We included randomised and quasi‐randomised clinical trials assessing tobacco cessation interventions conducted by dental professionals in the dental practice or community setting, with at least six months of follow‐up. DATA COLLECTION AND ANALYSIS: Two review authors independently reviewed abstracts for potential inclusion and extracted data from included trials. We resolved disagreements by consensus. The primary outcome was abstinence from all tobacco use (e.g. cigarettes, smokeless tobacco) at the longest follow‐up, using the strictest definition of abstinence reported. Individual study effects and pooled effects were summarised as risk ratios (RR) and 95% confidence intervals (CI), using Mantel‐Haenszel random‐effects models to combine studies where appropriate. We assessed statistical heterogeneity with the I(2) statistic. We summarised secondary outcomes narratively. MAIN RESULTS: Twenty clinical trials involving 14,897 participants met the criteria for inclusion in this review. Sixteen studies assessed the effectiveness of interventions for tobacco‐use cessation in dental clinics and four assessed this in community (school or college) settings. Five studies included only smokeless tobacco users, and the remaining studies included either smoked tobacco users only, or a combination of both smoked and smokeless tobacco users. All studies employed behavioural interventions, with four offering nicotine treatment (nicotine replacement therapy (NRT) or e‐cigarettes) as part of the intervention. We judged three studies to be at low risk of bias, one to be at unclear risk of bias, and the remaining 16 studies to be at high risk of bias. Compared with usual care, brief advice, very brief advice, or less active treatment, we found very low‐certainty evidence of benefit from behavioural support provided by dental professionals, comprising either one session (RR 1.86, 95% CI 1.01 to 3.41; I(2) = 66%; four studies, n = 6328), or more than one session (RR 1.90, 95% CI 1.17 to 3.11; I(2) = 61%; seven studies, n = 2639), on abstinence from tobacco use at least six months from baseline. We found moderate‐certainty evidence of benefit from behavioural interventions provided by dental professionals combined with the provision of NRT or e‐cigarettes, compared with no intervention, usual care, brief, or very brief advice only (RR 2.76, 95% CI 1.58 to 4.82; I(2) = 0%; four studies, n = 1221). We did not detect a benefit from multiple‐session behavioural support provided by dental professionals delivered in a high school or college, instead of a dental setting (RR 1.51, 95% CI 0.86 to 2.65; I(2) = 83%; three studies, n = 1020; very low‐certainty evidence). Only one study reported adverse events or oral health outcomes, making it difficult to draw any conclusions. AUTHORS' CONCLUSIONS: There is very low‐certainty evidence that quit rates increase when dental professionals offer behavioural support to promote tobacco cessation. There is moderate‐certainty evidence that tobacco abstinence rates increase in cigarette smokers if dental professionals offer behavioural support combined with pharmacotherapy. Further evidence is required to be certain of the size of the benefit and whether adding pharmacological interventions is more effective than behavioural support alone. Future studies should use biochemical validation of abstinence so as to preclude the risk of detection bias. There is insufficient evidence on whether these interventions lead to adverse effects, but no reasons to suspect that these effects would be specific to interventions delivered by dental professionals. There was insufficient evidence that interventions affected oral health.